Occurrence of green tobacco sickness and associated factors in farmers residing in Dom Feliciano Municipality, Rio Grande do Sul State, Southern Region of Brazil - Élida Campos; Vanessa Indio-; Sérgio Rabello Alves; Ana Cristina Simões Rosa; Bárbara Rodrigues Geraldino; Beatriz da Cruz Meira; Valéria Cunha; Tânia Maria Cavalcante; Silvana Rubano Turci; Marcia Sarpa; Ubirani Barros Otero (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2020)
Abstract: This study aimed to evaluate the occurrence of the green tobacco sickness (GTS) and its associated factors in tobacco familiar farmers residing in Dom Feliciano, Rio Grande do Sul State, Brazil. A cross-sectional study was conducted evaluating the sickness in 354 small tobacco farmers, between October 2011 and March 2012. The urinary concentration of cotinine, a biomarker of exposure to nicotine, was determined during the tobacco harvest period. Subjects presenting cotinine urinary levels ≥ 50ng/mL, that had contact with tobacco leaves up to 48 hours before the sample collection and reported at least one disease symptom were deemed as cases. A non-conditional logistic analysis was performed to evaluate the association between GTS and the population characteristics. A total of 122 (34.5%) cases were identified, with 39% of them being smokers and 61% being males. The median cotinine urinary concentrations were 75.6ng/mL (74.1ng/mg of creatinine) for non-cases and 755.8ng/mL (632.1ng/mg of creatinine) for the cases (p-value ≤ 0.01). The multivariate analysis showed a positive association between GTS and sunlight exposure time, exposure to pesticides, worse health status, and inverse association with wood cultivation. This study presented a high GTS prevalence and suggest that the use of urinary cotinine is a significant biomarker to determine GTS cases, influencing in the distribution by sex. Once the tobacco production involves health hazards, is important to implement measures to prevent the harm caused to tobacco farmers, as set in articles 17 and 18 of the World Health Organization Framework Convention on Tobacco Control.